Evaluation of common COL2A1 gene variants in Iranian patients suspected with Stickler syndrome type I - Fatemeh Abolhasani; Hossein Abdali; Mohammad Kazemi; Bijan Movahedian Attar; Fatemeh Derakhshandeh; Majid Hosseinzadeh (Journal of Research in Medical Sciences)
Background: Stickler syndrome, also known as hereditary progressive arthro-ophthalmopathy, is a connective tissue disorder that arises from mutations in multiple genes, each with distinct hereditary patterns. Stickler syndrome type I, which is inherited in an autosomal dominant manner, is specifically linked to mutations in the COL2A1 gene. The objective of this study is to investigate the prevalence of common variants of the COL2A1 gene among individuals suspected of having Stickler syndrome type I. Materials and Methods: Twenty-six Iranian patients suspected of having Stickler syndrome type I referring to Al-Zahra Hospital of Isfahan were employed in this cross-sectional study. The DNA was extracted from the patient’s peripheral blood samples, and the selected exons of the COL2A1 gene were amplified by polymerase chain reaction. Subsequently, the purified amplicons were subjected to Sanger sequencing to identify common variants associated with Stickler syndrome type I. Results: All patients exhibit cleft abnormalities (palate, lip, and alveolar), 84.6% of patients exhibit ocular abnormalities, 53.8% of patients exhibit hearing abnormalities, and 34.6% of patients exhibit skeletal abnormalities. As the data displays, the highest phenotype presentation prevalence rate was related to cleft lip and palate, while hemiparesis was the lowest clinical finding among the patients. Molecular analysis which conducted to screen the COL2A1 gene of patients, identified two different variants, including a novel nonsense variant, (c.1030C>T), consistent with dominantly inherited Stickler syndrome type I, also synonymous mutation (c.213C>T) affecting in exon 2, which have been reported in database. Conclusion: Genetic analysis of Twenty-six unrelated families with Stickler syndrome type I disorder discovered one novel pathogenic variant in the COL2A1 gene in a patient with Stickler syndrome type I. Genetic analysis is helpful for the diagnosis of this clinically variable and genetically heterogeneous disorder.